Temperature Monitoring System and pH Control of Catfish Breeding Pond Water Based on NodeMCU 8266 with Telegram Bot Notification - Irfan, Irfan Syaputra Sianturi; Junedi Ginting (Journal of Technomaterial Physics, 2022)
This research presents the design of a temperature monitoring and pH control device for catfish nurseries. The pH range of 6.5 to 8.5 with a temperature of 27â„ƒ to 31â„ƒ is the optimal condition for catfish farming. However, water quality can decrease due to unstable pH conditions and temperature changes. In this case, periodic monitoring is necessary to maintain stable pH and temperature conditions. This tool is constructed to monitor temperature and control water pH using DS18B20 temperature sensors, pH sensors, water pumps, Node MCU 8266, and a telegram application. This device is applied to maintain the stability of the pH of the water; pH control is carried out with a new water replacement method when the pH value is over the normal limit or is in acid and alkaline state. The new water replacement method is carried out by utilizing a water pump for the circulation process. When all components are well integrated into a system, including the whole program, then testing is carried out. Testing on this tool begins with turning on and running the system and observing the system's performance, dipping the temperature sensor and pH sensor probe into the water, and then observing the temperature and pH data displayed on the LCD. Furthermore, if the pH is in an acid or alkaline state, the pump will be active to carry out the process of circulating water replacement. The output of water temperature and pH measurements is displayed on the LCD and with Telegram notifications by sending messages or statuses on Telegram.